Intergenerational learning and Sikolohiyang Pilipino: Perspectives from the Philippines - Oropilla, Czarecah Tuppil; Guadana, Jean (Nordic Journal of Comparative and International Education (NJCIE), 2021)
Research on intergenerational learning delves into both the reciprocal transfer of knowledge and learning relationships between different generations. However, as this is an emerging research topic, there is a gap in the information available from various cultures. This paper aims to present intergenerational learning through the development of non-western indigenous psychology via the lens of Sikolohiyang Pilipino (Filipino psychology) in order to broaden the existing perspectives and understanding of intergenerational learning, engagements, and programs. By utilizing the theoretical framework of Sikolohiyang Pilipino, notably as espoused by Virgilio Enriquez, indigenous Filipino values are identified as key to understanding the predominance of family and community as venues and arenas for intergenerational learning in the Philippines. This underscores the importance of using the philosophical arguments associated with different cultural perspectives to challenge current assumptions and biases in intergenerational research and of being mindful when applying concepts that predominate in one culture to another. Additional intergenerational research in the Philippines will benefit from the inclusion of Sikolohiyang Pilipino as a theoretical framework since this will enable a deeper understanding of educational concepts within Filipino culture.